AB0982 Comparison of the Performance of the BASRI and Msasss in Patients with Early Inflammatory Back Pain from the DESIR Cohort. (10th June 2014) - de Hooge, M.; Claudepierre, P.; Feydy, A.; Reijnierse, M.; Saraux, A.; Dougados, M.; van der Heijde, D.
Abstract : Background: For assessing structural damage in AS on spinal X-rays Bath Ankylosing Spondylitis Radiology Index (BASRI) and modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS) scoring systems can be used Objectives: To present the prevalence of abnormalities based on the BASRI and mSASSS in patients (pts) with recent inflammatory back pain (IBP) and to compare these 2 scores Methods: Pts aged 18-50 with recent IBP (≥3 months, ≤3 years) from 25 participating centres in France were included in the DESIR (Devenir des Spondylarthropathies Indifferenciées Récentes)-cohort (n=708). Available baseline spinal X-rays (cervical and lumbar) were scored by 2 well-calibrated central readers independently, blinded for clinical data. When readers disagreed, an experienced radiologist served as adjudicator. BASRI and mSASSS were calculated from the mean of the scores of the 2 readers (and adjudicator if applicable). Pts were classified according to the ASAS axial SpondyloArthritis (ASAS axSpA) criteria into pts fulfilling the imaging arm, either fulfilling or not fulfilling the modified New York (mNY) criteria, fulfilling the clinical arm and not fulfilling (no-axSpA pts) the criteria Results: Pts with complete X-ray data (n=599) were included in these analyses. Overall, 559 pts (93.3%) had no definite abnormalities assessed by mSASSS <2, and 564 (94.2%) by BASRI <2; 93.0% and 93.5% within the ASAS axSpA group (n=431), respectively (see table). A BASRI of ≥2 was scored more frequently in the imaging arm compared to the clinical arm and no-axSpA pts (table). When comparing mSASSS and BASRI readings, using a cut-off of ≥2 (definite abnormalities) for both scoring methods, we found a very high percentage of agreement in all the different patient groups: range 95.4% to 98.2%. Only in few pts syndesmophytes were found (table). More syndesmophytes were present in cervical spine than in lumbar spine. The number of syndesmophytes in cervical vs lumbar spine was 6 vs 3 in the no-axSpA group, 6 vs 1 in the clinical arm, 5 vs 1 in the imaging mNY-group, and 8 vs 1 in the imaging mNY+ group Conclusions: The agreement between mSASSS and BASRI ≥2 is very high in all groups. Abnormalities typical for AS such as syndesmophytes are generally infrequent in this early cohort, but if observed, syndesmophytes are more frequent in the cervical spine compared to the lumbar spine. An mSASSS and BASRI of ≥2 is more often seen in pts fulfilling the ASAS classification criteria compared to no-SpA pts Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2662